Fostering interconnectivity dimension of low-carbon cities: The triple bottom line re-interpretation - Cam, Wynn Chi Nguyen (Habitat international, 2013)
In facilitating the progress towards low-carbon cities, there is no lack of available green technologies, planning techniques, economic tools, social development strategies, etc. These technologies, strategies and techniques have, in fact, long been deployed in many cities and communities around the world. However, the outcomes have been somewhat slow and less than expected. This is also manifested in the lower-than-expectation outcomes of the formation of a meaningful global climate change treaty so far. The barriers have clearly been unveiled as disconnection among the triple bottom lines (TBL) in the approach. By linking the concept of low-carbon cities to sustainable development (informed by the TBL), the paper highlights the implication of misinterpretation of a popular TBL diagram, leading to fragmented, compromised approach to LCC. Cases in point are isolating and excluding social and economic activities that are not environmental friendly, and trading-off environmentally-friendly activities that are not profitable in economic sense. Re-interpretation the popular TBL diagram literally from a three-dimensional lens offers an alternative approach, presented in an integrated framework towards low-carbon cities. The vital factors in the framework are safeguarding the positive dynamic interconnectivities of the three bottom lines, aligning their core values (in contrast to the isolating and excluding exercise), amplifying their common interest (instead of trading-off activities), and deploying strategies from planning, renewable technologies, education and policy making to address multiple and interconnected issues reciprocally. ► Positive connections among TBLs are important for low-carbon cities development. ► TBLs’ core values should be aligned, and not subject to excluding exercise. ► TBLs’ common interests should be optimised, to avoid trading-off activities. ► Strategies, addressing multiple issues, should be deployed in a reciprocal manner.